Digital Technology Leadership of School Administrators under the Secondary Educational Service Area Office Bangkok 1 - Sonpiam, Ratana; Dejbamrung, Sombat; Dejbamrung, Somchai; Chindapan, Arom (Journal for Developing the Social and Community, 2025)
Background and Aims: Digital technology has played a crucial role in driving the education system forward. Therefore, school administrators must possess digital technology leadership in order to manage and develop their institutions effectively. The ability to adapt to and implement technology is a key factor for the success of educational organizations in the 21st century. The objectives of this research article are: (1) to study the digital technology leadership of school administrators, (2) to explore approaches for promoting digital technology leadership among school administrators, and (3) to examine strategies for developing digital technology leadership in school administrators. Methodology: This study employed a mixed-methods research design. The sample consisted of 370 teachers from schools under the Office of the Secondary Educational Service Area Bangkok 1, selected using Taro Yamane’s sample size table and stratified random sampling. The research instruments included a questionnaire and a structured interview. The statistical methods used for data analysis were frequency, percentage, mean, standard deviation, and content analysis. Results: 1) The digital leadership of school administrators was found to be at a high average level. When considering each aspect, the highest average was in having a digital vision and digital communication, while the lowest was in digital literacy. 2) The guidelines for promoting digital leadership among school administrators are as follows: (1) Public relations with the aim of building a positive image; (2) Creating understanding through clear and easily understandable visual media; (3) Applying digital technology to support online learning and education; (4) Providing access to modern digital technology services; (5) Building the school’s digital technology image; (6) Increasing administrative efficiency through digital technology; (7) Developing strategic plans to implement digital technology effectively in operations; (8) Analyzing the current digital technology status of the school to develop strategies; and (9) Promoting the application of digital technology in student support systems. And 3) The guidelines for developing digital leadership among school administrators include: (1) Using digital technology to monitor teachers’ use of instructional media; (2) Using digital technology to create databases, plan, monitor staffing, and determine positions; (3) Using digital technology to effectively monitor the performance of school personnel; (4) Being aware of and keeping up with digital technology usage; (5) Selecting digital technology that appropriately meets the needs of the school effectively; and (6) Managing personal data efficiently and securely. Conclusion: All school administrators must recognize the value and importance of digital technology leadership in order to keep pace with 21st-century technology and future advancements. Without digital leadership, school operations will lack efficiency, effectiveness, and credibility in the eyes of the community and society. In particular, administrators under the jurisdiction of the Secondary Educational Service Area Office Bangkok 1 must cultivate digital leadership within themselves, among colleagues, as well as among parents and students, to keep up with the rapidly advancing digital technologies.